2009
DOI: 10.1167/iovs.08-2969
|View full text |Cite
|
Sign up to set email alerts
|

Poly-ε-Caprolactone Intravitreous Devices: An In Vivo Study

Abstract: This study demonstrates the feasibility and tolerance of intravitreous PCL drug delivery systems, which can offer a wide range of applications for intraocular drug delivery because of their controlled and prolonged release over months or even years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Fialho et al also developed poly-e-caprolactone (PCL) implants containing dexamethasone (Fialho et al, 2008;Fialho et al, 2009). These implants released dexamethasone concentrations in vitro, indicating their potential for suppressing several inflammatory processes.…”
Section: Biodegradable Implants In the Treatment Of Uveitismentioning
confidence: 99%
“…Fialho et al also developed poly-e-caprolactone (PCL) implants containing dexamethasone (Fialho et al, 2008;Fialho et al, 2009). These implants released dexamethasone concentrations in vitro, indicating their potential for suppressing several inflammatory processes.…”
Section: Biodegradable Implants In the Treatment Of Uveitismentioning
confidence: 99%
“…As dexamethasone is released, the polymer slowly degrades into carbon dioxide and water. 40 Since the implant dissolves completely, sequential implants can be placed into the eye over time without a need for surgical removal. Animal studies showed that the implants were well tolerated, the release of dexamethasone was gradual, and biodegradation was slow.…”
Section: Corticosteroid Implantsmentioning
confidence: 99%
“…Release of antibiotics, like gentamicin sulfate (Chang et al, 2008), minocycline (Kyun et al, 1990), amikacin Prabu et al, 2006), gatifloxacin (El-Kamel & Baddour, 2007), and dexamethasone (Silva-Cunha et al, 2009), from PCL-PLA or PLA matrices, has been studied for applications in conditions like osteomyelitis, periodontitis, and as implants for intravitreous administration. Hormonal delivery has also been studied using PCL, primarily due to its long degradation time.…”
Section: Introductionmentioning
confidence: 99%